MAKNA AYUNAN REJUNG PADA MASYARAKAT PULAU BERINGIN - Silo Siswanto (Besaung : Jurnal Seni Desain dan Budaya, 2017)
Rejungan is the another name of batanghari sembilan based on the writing of firmansyah the name of batang harii sembilan music as a new thing for listener and actor the society pagaralam and semende its not only as same as melody but it has philosophy is in the music . it can clarified that rejung is not only a art of music based on art experienced only but rejung as a result of representation or reflection from society habitual in semende ethnic.Ayunan umak and ayunan anak in the music rejung became a media of communication for society of semende ethnic either as a medium of entertainment or as a medium of learning to aquentance value of religion whereas the value of customs for childern and society semende ethnic with the religious leaders although the customary leaders because of ayunan became important thing to rejung it means the word ayunan has own meaning for society semende ethnic. The result of research that got comprehesion to philosophy ayunan rejung it has the value of localwisdomKeywords : Rejung – ayunan – meaning – society of pulau beringin